An on-demand gas segmented flow generator with high spatiotemporal resolution for in vivo analysis of neuronal response in C. elegans. Issue 20 (22nd September 2016) - Hu, Liang; Ge, Anle; Wang, Xixian; Wang, Shanshan; Gao, Yue; Feng, Xiaojun; Du, Wei; Liu, Bi-Feng
Abstract : We report an on-demand gas segmented flow generator with high spatiotemporal resolution to analyze neuronal responses of C. elegans to fluctuating gas cues. Abstract : Studies of chemo-sensing in C. elegans to fluctuating gaseous cues are limited due to the lack of a method of precise gas control. In this paper, we describe a microfluidic-based on-demand gas segmented flow generator for performing fluctuating gaseous stimulations to worms. This highly versatile and programmable micro-device integrated with pneumatic valves for flexible and stable gas flow control and worm immobilization enabled us to examine the temporal features of neuronal response to multiple gas pulses with sub-second precision. As a result, we demonstrated the capability of the micro-device to generate repetitive gaseous chemical pulses with varying durations. By characterizing intracellular calcium signals, we showed that URX sensory neurons were sensitive to O2 pulses with duration of more than 0.5 s. Furthermore, URX neuronal adaptation and recovery in response to gaseous chemical pulses were investigated by varying the durations and intervals. The developed microfluidic system is shown to be a useful tool for studying the dynamics of in vivo gas-evoked neuronal responses and revealing the temporal properties of environmental stimulations.